Présentation de la nomenclature des préjudices réparables en cas d'atteintes à l'environnement - Aude-Solveig Epstein (VertigO)
French law has nowadays widened the possibilities to take into account the consequences of environmental damage. Not solely classical personal injuries caused via the environment (environment-related damage) but also damage to the environment itself are from now on taken into account. But the remediation of environmental damage suffers because of the difficulty to identify clearly the different types of damage that should be taken into consideration. The outcome is the existence on the one hand of contact zones between several damage types, at the risk of setting of a double compensation for a single damage and on the other hand of shadow zones, which mean that although there is a real damage, there won’t be any remediation. Another consequence is that we are facing a remediation that varies according to circumstances, to jurisdictions and to concerned institutions. In order to put an end to this situation and to guarantee the respect of essential principles such as integral remediation, judicial security and equality, we must move towards a structured typology of the remediable environmental damage. The drawing up of such a typology is precisely the objective of the working group animated by the professor G. J. Martin and Laurent Neyret, and hosted by Sciences-po Paris. This typology of the remediable environmental damage, which is being drafted on a participative basis, may be an operational instrument able to guide the different protagonists of environmental action (lawyers, magistrates, operators of polluting activities, insurers, environmental experts, environmental defenders…).